Reconstruction of the insulin-like signalling pathway of Haemonchus contortus. Issue 1 (December 2016) - Mohandas, Namitha; Hu, Min; Stroehlein, Andreas; Young, Neil; Sternberg, Paul; Lok, James; Gasser, Robin
Abstract Background In the present study, we reconstructed the insulin/insulin-like growth factor 1 signalling (IIS) pathway forHaemonchus contortus, which is one of the most important eukaryotic pathogens of livestock worldwide and is related to the free-living nematodeCaenorhabditis elegans . Methods We curated full-length open-reading frames from assembled transcripts, defined the complement of genes that encode proteins involved in this pathway and then investigated the transcription profiles of these genes for all key developmental stages ofH. contortus . Results The core components of the IIS pathway are similar to their respective homologs inC. elegans . However, there is considerable variation in the numbers of isoforms betweenH. contortus andC. elegans and an absence of AKT-2 and DDL-2 homologs fromH. contortus . Interestingly, DAF-16 has a single isoform inH. contortus compared with 12 inC. elegans, suggesting novel functional roles in the parasitic nematode. Some IIS proteins, such as DAF-18 and SGK-1, vary in their functional domains, indicating distinct roles from their homologs inC. elegans . Conclusions This study paves the way for the further characterization of key signalling pathways in other socioeconomically important parasites and should help understand the complex mechanisms involved in developmental processes.